COMPARATIVE ANALYSIS OF WALNUTS AND PEANUTS OILS - NIȚU, Sabina; PĂDURE, Mirabela; TĂMĂȘ, Andra; RUSNAC, Lucian Mircea (Studia Universitatis Babeș-Bolyai Chemia, 2019)
In this paper, a comparative study of the physico-chemical properties and composition of walnuts and peanuts oils obtained by cold pressing or Soxhlet extraction in hexane was performed. The physical properties (color, density, refractive index, acidity, saponification, iodine and peroxide values, rheological behavior), the distribution of the major fatty acids in oils (through gas-chromatographic analysis) and the metal content were determined.